The effectiveness of magazine advertising - Consterdine, Guy (Henry Stewart Talks, 2009)
Readers develop a personal relationship with their magazines, Magazines are well read, Readers are receptive to the advertising, Magazine advertising influences the purchase decision-making process, Magazines make digital media and buzz work harder -Magazine advertising creates sales
Archived at 2022/11/27